Protracted social conflicts as preconditions for secessionist movements of the Iraqi Kurds (International relations and international law Journal, 2021)
Protracted social conflicts can serve as the basis for separatist or secessionist movements in certain states. As a result of protracted social conflicts in a separate state arise such phenomena as civil war, genocide, «national cleansing», separatist wars.Although there are enough studies explaining the essence and nature of such protracted social conflicts, nevertheless, there are not so many studies that can explain in detail the prerequisites for the emergence of such a phenomenon of protracted social conflicts as the studies of E. Azar. In this study, authors tried to explain the prerequisites for the emergence of the Iraqi Kurdish secessionist movement based on the concept of protracted social conflicts by E. Azar. As an analytical criterion of the study, the following elements were selected – communal content of groups, deprivation of human needs of groups, governance and the state’s role, as well as international linkages.According to the conclusion of the research analysis, firstly, the Iraqi Kurds managed to maintain their potential power as a political group for a long time. Secondly, the Iraqi government could not meet the basic needs of the Kurds. Thirdly, the Iraqi government has isolated the Kurds in the process of governance and political decision-making. Fourth, regional and international powers such as Turkey and tht United States, by providing support, allowed the Kurds to take a decisive step towards creating a secessionist movement.Key words: protracted social conflicts, secessionism, nationalism, Iraqi Kurds, ethnic conflict.